The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1016/s0960-9822(06)00339-3
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-2 influences axonal growth rate in embryonic sensory neurons

Abstract: Bcl-2 plays a key role in regulating cell survival in the immune and nervous systems. Mice lacking the bcl-2 gene have markedly reduced numbers of B and T cells as a result of increased apoptosis, whereas mice with a transgene causing high levels of Bcl-2 expression in the immune system show extended survival of B and T cells. Overexpression of Bcl-2 in cultured neurons prevents their death following neurotrophin deprivation, and mice with a bcl-2 transgene under the control of a neuron-specific enolase promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
2
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 24 publications
3
37
2
1
Order By: Relevance
“…A growing body of data is also showing that, in addition to its well established neuroprotective effects, bcl-2 may also exert independent neurotrophic effects. Thus, Bcl-2 overexpression has also been shown to promote regeneration of axons in the mammalian CNS, 91 to regulate neurite sprouting and outgrowth, 91 and to increase axonal growth rate, 92,93 effects which may all be independent of its anti-apoptotic effects. Importantly for the present discussion, bcl-2 has also been demonstrated to rescue cells from toxin-induced cell atrophy; 94 it has thus been convincingly argued that increasing CNS Bcl-2 levels may represent a very effective neurotrophic strategy to enhance cellular resiliency.…”
Section: (Vide Infra)mentioning
confidence: 99%
“…A growing body of data is also showing that, in addition to its well established neuroprotective effects, bcl-2 may also exert independent neurotrophic effects. Thus, Bcl-2 overexpression has also been shown to promote regeneration of axons in the mammalian CNS, 91 to regulate neurite sprouting and outgrowth, 91 and to increase axonal growth rate, 92,93 effects which may all be independent of its anti-apoptotic effects. Importantly for the present discussion, bcl-2 has also been demonstrated to rescue cells from toxin-induced cell atrophy; 94 it has thus been convincingly argued that increasing CNS Bcl-2 levels may represent a very effective neurotrophic strategy to enhance cellular resiliency.…”
Section: (Vide Infra)mentioning
confidence: 99%
“…Thus, a swap of a 23 aminoacid segment surrounding BH3 from Bax into Bcl-2 converted Bcl-2 from a death antagonist to a death agonist . (Nakayama et al, 1994) Lymphopenia (Nakayama et al, 1994) Accelerated G1-S cell cycle progression in T cells (Linette et al, 1996) Multicystic kidney, renal hypoplasia and renal failure (Nakayama et al, 1994;Sorenson et al, 1996) Gray hair due to accelerated loss of melanocytes (Yamamura et al, 1996) Decrease in the number of oocytes and primordial follicles (Ratts et al, 1995) Distorted small intestine with accelerated exfoliation of epithelial cells (Kamada et al, 1995) Degeneration of motoneurons, sympathetic, and sensory neurons during early postnatal development (Michaelidis et al, 1996) Enhanced susceptibility of cerebellar granule neurons to undergo apoptosis in vitro (Tanabe et al, 1997) Reduced axon growth rate in embryonic sensory neurons culutured in vitro (Hilton et al, 1997) Bcl-X Intrauterine death (E13) (Motoyama et al, 1995) Massive death of postmitotic immature neurons (Motoyama et al, 1995) Shortened life-span of immature lymphocytes (Motoyama et al, 1995) Enhanced death of serum-depleted telencephalic cells in vitro Bxl-w Sterility with progressive testicular degeneration, blockade in late spermiogenesis (Ross et al, 1998) (Deckwerth et al, 1996) More neurons in cervical ganglia and facial nuclei (Deckwerth et al, 1996) Prevents increased cell death of immature neurons in Bcl-X 7/7 mice (Shindler et al, 1997) Asymmetric receptor/ligand interactions among members of the Bcl-2 family Mutagenesis studies and NMR data revealed that intact BH1, BH2 and BH3 domains of the antagonists (Bcl-2, Bcl-X L ) are required for them to heterodimerize with the BH3 domain of Bak or Bax and to repress cell death (Sattler et al, 1997;Sedlak et al, 1995;Ying et al, 1994). It appears that the BH3 region forms and a helix which nestles into a crevice formed by the apposition of the BH1, BH2 and BH3 regions (Sattler et al, 1997).…”
Section: Bcl-2 Homology Regionsmentioning
confidence: 99%
“…However, the regeneration in CNS tracts has not proved to be satisfactory due to the meager axonal growth rate of adult neurons [4,5] and neurite retraction after a short time if no synaptic connection has been reached [6]. In addition, astrocyte activation after trauma leads to a glial scar which, though advantageous in preventing the lesion from spreading, is detrimental for the reconnection of neural populations [7].…”
Section: Introductionmentioning
confidence: 99%